PLASMA APHERESIS PROCEDURE - Ajit Pal Singh; Rahul Saxena; Suyash Saxena (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
The present study investigates to prepare single donor Plasma Apheresis product in the blood center with the help of Fresenius Cell Separator for use in patientwho require coagulation factors, covid patients, dengue patients etc. Apheresis is a medical procedure that involves removing whole blood from a donor or patient and separating the blood into individual components so that one particular component can be removed.Apheresis is a medical procedure that involves removing whole blood from a donor or patient and separating the blood into individual components so that one particular component can be removed. The remaining blood components then are re-infused back into the bloodstream of the patient or donor. Apheresis is also called pheresis or hemapheresis. The terminology used may also reflect the component of blood that is being removed, such as: Plasma (plasmapheresis) Platelets (plateletpheresis) Leukocytes (leukapheresis or leukopheresis) Lymphocytes (lymphopheresis or lymphapheresis) Red blood cells (erythropheresis) Total plasma exchange (removal of plasma and replacement with fresh frozen plasma) can also be performed using the apheresis procedure. It is also used for the collection of stem cells from the peripheral blood.